Qualitative methodology : a practical guide - Mills, Jane (Jane Elizabeth); Birks, Melanie (2014)
This textbook provides an introduction to the application of qualitative methodology in the real world. Researchers then trace the history and philosophical underpinnings of different methodologies, explore the specific demands each places upon the researcher and set out relevant issues surrounding quality and rigor. Featured methodologies include action research, discourse analysis, ethnography, grounded theory, case studies and narrative inquiry. This book provides a guide to the research process - it introduces the relevant methods of generating, collecting and analysing data for each discrete methodology and then looks at best practice for presenting findings. This enables new researchers to compare qualitative methods and to confidently select the approach most appropriate for their own research projects.
Introducing qualitative research / Jane Mills and Melanie Birks -- Practical philosophy / Melanie Birks -- Methodology and methods / Jane Mills -- Action research / Bob DIck -- Discourse analysis / Marianne LeGreco -- Critical ethnography / Urmitapa Dutta -- Grounded theory / Jane Mills, Melanie Birks, and Karen Hoare -- Historical research / Seán L'Estrange -- Case study Allison Stewart -- Narrative research / Patrick John Lewis and Robin Adeney -- Phenomenology / Kim Usher and Debra Jackson -- Proposing your research / Jane Mills and Melanie Birks -- Quality in qualitative research / Melanie Birks -- A new generation of qualitative research / Jane Mills.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Qualitative research; Qualitative research; Social sciences -- Research -- Methodology; Qualitative Methode; Qualitative Sozialforschung; Praxis; Society